2021
DOI: 10.1016/j.resmer.2021.100822
|View full text |Cite
|
Sign up to set email alerts
|

Severe SARS-CoV-2 pneumonia: Clinical, functional and imaging outcomes at 4 months

Abstract: Introduction: Given the pathophysiology of coronavirus disease 19 (COVID-19), persistent pulmonary abnormalities are likely. Methods:We conducted a prospective cohort study in severe COVID-19 patients who had oxygen saturation <94% and were primarily admitted to hospital. We aimed to describe persistent gas exchange abnormalities at 4 months, defined as decreased diffusing capacity of the lungs for carbon monoxide (DLco) and/or desaturation on the 6-minute walk test (6MWT), along with associated mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
2
16
0
1
Order By: Relevance
“…We also found that an impaired exercise capacity was associated with a lower lung function and particularly with a decrease in lung volume that characterized COVID-19 survivors [ 8 , 9 , 22 , 30 , 31 ]. A reduction of gas transfer measured by DL CO was also present, but this difference disappeared when this value was related with alveolar ventilation (K CO ), confirming the restrictive pulmonary pattern in patients presenting a decreased effort capacity.…”
Section: Discussionmentioning
confidence: 79%
“…We also found that an impaired exercise capacity was associated with a lower lung function and particularly with a decrease in lung volume that characterized COVID-19 survivors [ 8 , 9 , 22 , 30 , 31 ]. A reduction of gas transfer measured by DL CO was also present, but this difference disappeared when this value was related with alveolar ventilation (K CO ), confirming the restrictive pulmonary pattern in patients presenting a decreased effort capacity.…”
Section: Discussionmentioning
confidence: 79%
“…Indeed, this technique allows distinguishing between reductions of alveolar membrane diffusive conductance (D M ) and pulmonary capillary blood volume (V C ) [3] , [4] , [5] . Noel-Savina and collaborators reported a slight decrease in median V C in their cohort, and a preserved median D M [1] . This result drew our attention, because the opposite was found in two other monocentric series in which patients were reassessed after in-hospital treatment for COVID-19 pneumonia: one Italian study with 94 patients [6] , and one Spanish work with 200 subjects [7] .…”
mentioning
confidence: 86%
“…TO THE EDITOR: We read with great interest the article of Noel-Savina and collaborators, from Toulouse university hospital (France), about the outcomes of 72 patients with coronavirus disease 2019 (COVID-19) pneumonia, at 4 months after hospital discharge [1] . In their monocentric cohort, 76% of patients were admitted to intensive care unit.…”
mentioning
confidence: 99%
“…This finding indicates that SARS-CoV-2 infection strongly affects processes that are specific to small vessels [126] . It is particularly noteworthy that one study observed the persistence of vascular dysfunction in patients convalescing from Covid-19 [127] – possibly due to the persistence of ACE2 activity in plasma [128] and a lasting reduction in capillary volume [129] .…”
Section: Putative Mechanisms Underlying Met's Protective Effectsmentioning
confidence: 99%